2020
DOI: 10.1002/ctm2.156
|View full text |Cite
|
Sign up to set email alerts
|

A three‐lncRNA signature of pretreatment biopsies predicts pathological response and outcome in esophageal squamous cell carcinoma with neoadjuvant chemoradiotherapy

Abstract: Background Current strategies are insufficient to predict pathologically complete response (pCR) for esophageal squamous cell carcinomas (ESCCs) before treatment. Here, we aim to develop a novel long noncoding RNA (lncRNA) signature for pCR and outcome prediction of ESCCs through a multicenter analysis for a Chinese population. Methods Differentially expressed lncRNAs (DELs) between pCRs and less than pCR ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Up-regulation of PRKAG2-AS1 was detected in HCC than normal tissue specimens. As previous studies, this lncRNA could be overexpressed in colon adenocarcinoma (13), advanced prostate cancer (14) and esophageal squamous cell carcinoma (15). Our data suggested that PRKAG2-AS1 up-regulation was suggestive of poor OS and DFS.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Up-regulation of PRKAG2-AS1 was detected in HCC than normal tissue specimens. As previous studies, this lncRNA could be overexpressed in colon adenocarcinoma (13), advanced prostate cancer (14) and esophageal squamous cell carcinoma (15). Our data suggested that PRKAG2-AS1 up-regulation was suggestive of poor OS and DFS.…”
Section: Discussionsupporting
confidence: 78%
“…Thus, PRKAG2-AS1 could be a promising prognostic factor for HCC. Previously, PRKAG2-AS1 has been identified as a prognostic marker for colon adenocarcinoma (13), advanced prostate cancer ( 14) and esophageal squamous cell carcinoma (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, some of the irlncRNAs in the process of modeling that have been already identi ed play an important role in malignant phenotypes of various cancer types, such as LINC01063 [24,25], HOXC-AS1 [26,27], LINC02454 [28,29] and SCAT1 [30]. Furthermore, previous reports have shown that LINC00460 [31], C5orf66-AS1 [32] and TMPO-AS1 [33] are associated with prognosis and treatment outcomes in HNSCC.…”
Section: Discussionmentioning
confidence: 75%
“…Emerging studies suggest that robust prediction of patient response to CCRT could also be achieved by using a variety of other methodologies, including molecular signature, CT-radiomics, and positron emission tomography. [41][42][43] Combining these markers with PBCS may lead to a greater predictive capability for patient outcomes.…”
Section: Dovepressmentioning
confidence: 99%